Sensory Quality and Hedonic Level of Sigararutang Arabica Coffee Brew on Varied Processing Treatment - Purba, Hendri Ferianson P; Deliana P, Agriawati; Tommy, Purba; Perdinanta, Sembiring; Khadijah EL, Ramija; Nurmalia; Alfonso, Sitorus; Nurhafsah; David Jhon, Haloho; Justus Elisa, Loppies (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Abstract Sigarar Utang as one of Indonesia’s Arabica coffees has superior characteristics such as delicious taste, large bean size and pest resistant. Coffee quality is set during cultivation, but post-harvest processing has a significant impact. Independent processing efforts to generate specialty coffee at the farmer level have the potential to improve farmer welfare. This study aimed to: 1) determine the potential of dry and wet processing (Full wash, Semi wash, Natural, Honey, and Wine) in producing Sigarar Utang specialty coffee and 2) determine the effect of processing and roasting types on consumer preferences. The research was conducted in Gurgur, Toba Samosir Regency, and the Post-Harvest Laboratory of AIAT North Sumatra. The results showed that 4 out of 5 types of processing were able to produce specialty Sigarar Utang coffee. The cupping test results for each processing method were as follows: 85.25 for full and semi wash, 84.75 for honey, 84.5 for natural, and 78.13 for wine. Based on the hedonic test, the highest taste and aroma preferences for each method were 66.6 and 61.9% for light roasting in honey and semi-wash processing; 2) 72.3 and 63.6% for medium roasting in full and semi-wash processing; 3) 63.4 and 81.1% for dark roasting in honey and semi-wash processing and natural and honey. The Friedman test results revealed that the processing method had only a significant effect on the level of preference for the aroma of dark roasted coffee.